Performance analysis of evacuated tubes coupled solar still with double basin solar still and solid fins. Issue 9 (28th July 2020) - Panchal, Hitesh; Kumar Sadasivuni, Kishor; Suresh, M.; Yadav, Satyapal; Brahmbhatt, Shivani
ABSTRACT: Experimental set up of double basin solar still with evacuated tubes has been fabricated by locally available materials and then carry out research work by use of solid fins. Here 2.5 cm constant depth of water maintained and 3 cm depth mild steel fins are used. Experimental results have been obtained during month of March and April 2018 during clear sky days. Month of March 2018 is chosen for experiments on double basin solar still with evacuated tubes only and April 2018 is chosen for experiments on double basin solar still with evacuated tubes and fins. After series of experiments, it has been found that, the fins increase 25% distillate output compared with alone double basin solar still with evacuated tubes. It also increases distillate output during sunshine hours as well as off-sunshine hours.